Detection of hepatitis B surface antigen among Scottish blood donors: evaluation of sensitive tanned-cell haemagglutination-inhibition test. Issue 5968 (24th May 1975) - Hopkins, R; Robertson, M; Ross, D; Turnbull, W M; Das, P C
Abstract : A total of 70 224 blood donations were tested at three Scottish blood transfusion centres for hepatitis B surface antigen /HBsAg) by an economical haemagglutination-inhibition method (E.H.A.I.) and the results compared with those of counterelectrophoresis (C.E.P.). A further 4086 donations were tested using the Wellcome turkey cell haemagglutination test, C.E.P., and E.H.A.I.E.H.A.I. was also compared with commercial haemagglutination and radioimmunoassay reagents for sensitivity and specificity against several established antigen panels and used to reinvestigate counterelectrophoresis-negative blood donations implicated in post-transfusion hepatitis. E.H.A.I. combines the inherent specificity of an inhibition reaction with a sensitivity equal to that of commercial radioimmunoassay and haemagglutination kits but at a fraction of the cost. The assessment of 70 224 blood donations in three regions showed that E.H.A.I. detected more antigen-positive blood donations than C.E.P. Results of retesting more than 100 blood donors implicated in 10 cases of post-transfusion hepatitis suggested that the use of E.H.A.I. or a test of similar sensitivity in place of C.E.P. may significantly reduce the incidence of this complication.